Pharmacological treatment of Restless Legs Syndrome: a systematic review and critical appraisal - Gonçalves, Catarina Abrantes (2016)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2015